The Effect of the Teams Games Tournament (TGT) Model and Motivation on Understanding Pancasila Philosophy - Suryanto, Hadi; Ghofur, Abd; Zaman, Akhmad Qomaru (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The effect of the Teams Games Tournament learning model and motivation on understanding the ideology of Pancasila in the Civics Study Program was studied using a non-equivalent group pretest-posttest research design. The PPKN study program, totalling 30 people, was the subject of this research. Questionnaires and tests are used to gather information about research findings. The research investigation was carried out using the independent sample t-test technique, with a significance level 0.05. The study's findings show that the total count is 5.509. Here, the t value exceeds the 2.048 t table value. These findings suggest that cooperative learning models of the TGT kind effect student learning motivation. Based on the Independent Samples Test on "Assumption of Equal variances," the Sig is known. (2-tailed) of 0.000 < 0.05 to be the basis for decision-making in the Independent Sample T-Test. As a result, there is a relatively significant difference in learning outcomes between students taught using the conventional learning model (control class) and students taught using the TGT learning model. The Pancasila ideology is different in applying the Teams Games Tournament learning model to the standard learning model. Second, the Teams Games Tournament learning style can increase learning motivation because of active participation.